Decreased levels of matrix metalloproteinase-2 in root-canal exudates during root canal treatment - Pattamapun K. (2017)
© 2017 Elsevier Ltd Objective To determine the matrix metalloproteinase-2 (MMP-2) levels in root-canal exudates from teeth undergoing root-canal treatment. Material and methods The root-canal exudates from six teeth with normal pulp and periradicular tissues that required intentional root canal treatment for prosthodontic reasons and from twelve teeth with pulp necrosis and asymptomatic apical periodontitis (AAP) were sampled with paper points for bacterial culture and aspirated for the detection of proMMP-2 and active MMP-2 by gelatin zymography and the quantification of MMP-2 levels by ELISA. Results By gelatin zymography, both proMMP-2 and active MMP-2 were detected in the first collection of root-canal exudates from teeth with pulp necrosis and AAP, but not from teeth with normal pulp, and their levels gradually decreased and disappeared at the last collection. Consistently, ELISA demonstrated a significant decrease in MMP-2 levels in the root-canal exudates of teeth with pulp necrosis and AAP following root canal procedures (p  <  0.05). Furthermore, the MMP-2 levels were significantly lower in the negative bacterial culture than those in the positive bacterial culture (p  <  0.001). Conclusions The levels of MMP-2 in root-canal exudates from teeth with pulp necrosis and AAP were gradually reduced during root canal procedures. Future studies are required to determine if MMP-2 levels may be used as a biomolecule for the healing of apical lesions, similar to the clinical application of MMP-8 as a biomarker.